Characterisation of a highly polymorphic microsatellite at the DXS207 locus: confirmation of very close linkage to the retinoschisis disease gene. Issue 4 (April 1993) - Oudet, C; Weber, C; Kaplan, J; Segues, B; Croquette, M F; Roman, E O; Hanauer, A
Abstract : Juvenile retinoschisis (RS) is an X linked recessive vitreoretinal disorder for which the basic molecular defect is unknown. The gene for RS has been previously localised by linkage analysis to Xp22.1-p22.2 and the locus order Xpter-DXS16-(DXS43, DXS207)-RS-DXS274-DXS41-Xcen established. To improve the resolution of the genetic map in the RS region, we have isolated a highly polymorphic microsatellite at DXS207, which displays at least nine alleles with a heterozygosity of 0.83. Using this microsatellite and four other Xp22.1-p22.2 marker loci, DXS16, DXS43, DXS274, and DXS41, we performed pairwise and multilocus linkage analysis in 14 kindreds with RS. The microsatellite was also typed in the CEPH (Centre d'Etude du Polymorphisme Humain) reference families. Tight linkage was found between RS and DXS207 (Z(theta) = 14.32 at theta = 0.0), RS and DXS43 (Z(theta) = 8.10 at theta = 0.0), and DXS207 and DXS43 (Z(theta) = 40.31 at theta = 0.0). Our linkage results combined with data previously reported suggest that the DXS207-DXS43 cluster is located less than 2 cM telomeric to the RS locus. The microsatellite reported here will be a very useful marker for further linkage studies with retinoschisis as well as with other diseases in this region of the X chromosome.